Oral Presentations 1981
DOI: 10.1055/s-0038-1652564
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Platelet Interaction: The Effect On Platelet Cholesterol Content And Platelet Function

Abstract: Intracellular cholesterol metabolism is regulated by membrane receptors which selectively bind plasma low density lipoproteins (LDL), the major extracellular source of cholesterol. Human platelets, unlike other cells, are unable to synthesize cholesterol, but bind LDL with specificity. We have shown that very low density lipoproteins (VLDL) and LDL, both of which contain apolipoprotein B compete with 125I-LDL for the platelet binding sites, while high density lipoproteins (HDL) is only able to compete to a lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…HDL was found to have the opposite effect [2][3][4][5], Our present study was undertaken to char acterize more fully the effect of the plasma lipoproteins on aggregation and release of the GFP. The latter were employed in order to study the direct effect of the lipoproteins on the platelets without the influence of other plasma constituents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDL was found to have the opposite effect [2][3][4][5], Our present study was undertaken to char acterize more fully the effect of the plasma lipoproteins on aggregation and release of the GFP. The latter were employed in order to study the direct effect of the lipoproteins on the platelets without the influence of other plasma constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in hypercholesterolemic patients (phenotype Ila) with raised plasma low density lipoprotein (LDL) levels, increased in vivo [18,23] and in vitro [22] platelet activation has been shown. A decreased plasma high density lipoprotein (HDL) concentration associated with a sig nificant increase in platelet aggregation has been noted in females taking oral contracep tives [9], Aviram et al [1] have demonstrated that human platelets possess receptors for plasma lipoproteins and that in vitro thrombin-in duced platelet aggregation is profoundly af fected by the presence of plasma lipoproteins [2]. Incubation of very low density lipopro teins or low density lipoprotein with gel-fil tered platelets (GFP) results in increased thrombin induced platelet aggregation and l4C-serotonin release, whereas incubation with HDL has the opposite effect [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ruíz-Sandoval and coworkers found that hypocholesterolemia was more common in young patients (below the age of 20 years) with hemorrhagic stroke and in those who have been diagnosed with a cryptogenic type of intracerebral hemorrhage (24). The precise mechanism behind this increased risk of intracerebral hemorrhage in patients with hypolipidemia is unclear; a high diastolic blood pressure might work with low serum cholesterol to weaken the endothelium of intracerebral arteries or that hypocholesterolemia might result in platelet hypo-activity and dysfunction (3,25).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of LDL to platelets has been found to result in an increase in platelet cholesterol. 35 ' 36 A similar increase in platelet cholesterol has resulted from incubation of platelets with cholesterol-rich lipo somes. 37 Fatty acid content of the platelet membrane quantitatively parallels that of the lipoprotein 38 and a positive correlation between platelet cholesterol con tent and plasma cholesterol concentration as well as between the cholesterol to phospholipid ratio in the platelets and LDL has been found.…”
Section: Fig 4 Effect Of Ldl Vldl Hdl Chd-ldl and Albumin On Plmentioning
confidence: 96%